Peningkatan Peran Pemilih Pemula dalam Penyelenggaran Pemilihan Kepala Daerah Tahun 2024 - Robyan Bafadal (Universitas 45 Surabaya, 2024)
On November 27 2024, regional head elections will be held simultaneously. In the Indonesian political system, this is the first simultaneous election. In this election, based on the voter list, many novice voters were involved, namely those who were involved in voting for the first time. New voters are the future of democracy in Indonesia. Therefore, their involvement in elections is encouraged more than just voting but also being involved as election organizers. This is very important for competency development and network expansion in the future. This activity is an outreach regarding registration as an election organizer. The participants in this activity were ITSKKes Muhammadiyah Selong students. As a result of this activity, students were enthusiastic in understanding the voter registration process.